Recital słowo, humoru i piosenki Łukasza Łukaszewicza. ([S.l. : s.n.], 1946)
Program recitalu.
Keywords: Życie artystyczne -- Polska -- Gdynia -- 1945-1970.; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła